한국 노인의 성공적 노후 개념에 대한 암시적 타당화 - 주민경(Min-Kyoung Joo); 송선희(Sun-Hee Song) (한국콘텐츠학회 논문지, 12(2), 2012)
The purpose of the this research is to find out what basic factors of aging for korean elderly(above 65years old). First of all, 90 preliminary questions were developed from 551 questionnaires. In addition, some practices of the composition factors were carried out from another 552 seniors and additional tests were tried for composition validity, certified validity and successful aging standards from other 399 elders. The survey showed that the standard of the successful aging for korean elderly, which was composed of 47 questions, displayed satisfaction of everyday life, off-spring's success, psychological support, positive activity. sense of self effectiveness, mental stability, satisfaction of spousal relationship and family support. The reliability of the Validation of Successful Aging for Korean Elderly showed high internal consistency of 0.932. It is also verified that the relationship between the factors and the questions has statistically meaningful, which makes it possible to confirm the reliability of the structure of the factors. 본 연구에서는 65세 이상의 한국노인을 대상으로 노후 개념의 원형적 요인들은 무엇인지 알아보고, 그 원형의 개념 추출을 위해 511명을 대상으로 무선 표집하여 90문항의 2차 예비척도 문항 개발하였고, 2차552명을 대상으로 구성요인 확인, 3차 399명을 대상으로 구성타당도, 그리고 공인타당도, 성공적 노후척도와 성별, 연령, 학력에 따른 차이 검증을 실시하였다. 그 결과 '한국노인의 성공적 노후 척도'는 총 47문항으로 '일상적 삶의 순조로움', '자녀성공', '경제적 안정', '심리적 지지', '적극적 활동', '부부관계만족', '가족지지'와 같은 7개의 요인으로 구성됨을 확인하였다. 그리고 한국노인의 성공적 노후의 신뢰도는 .932로 높은 내적 일치도를 보였고, 탐색적 요인분석을 통해 요인과 문항 간의 관계가 통계적으로 유의미함을 확인하여 요인구조에 대한 타당도를 확인하였다.